Mapping the Relative Risk of Tuberculosis in Indonesia Using the Bayesian Spatial Conditional Autoregressive Leroux Model - Aswi, Aswi; Nurhikmawati, Nurhikmawati; Shanty, Meyrna Vidya; Herman, Nur Taj Alya’; Sukarna, Sukarna (Journal of Mathematics, Computations and Statistics, 2025)
Tuberculosis (TB) is an infectious disease caused by infection with the Mycobacterium Tuberculosis bacteria. Indonesia ranks second globally in terms of the number of TB cases, after India, followed by China. Modeling is needed to evaluate the relative risk (RR) of TB cases in Indonesia to identify areas that have a high RR of being infected with the bacteria. One approach used to estimate the RR of TB in Indonesia is Bayesian Conditional Autoregressive (CAR). This research aims to identify the RR rate of TB cases in Indonesia using the Bayesian spatial CAR Leroux approach based on TB case data from 2021 to 2022. The best model selection is based on Deviance Information Criteria values, the Watanabe Akaike Information, and residuals from Modified Moran's I. Analysis results shows that in 2021, the Bayesian spatial CAR Leroux Model with Inverse Gamma prior (0.5; 0.5) is the best model. DKI Jakarta Province has the highest while Bali Province has the lowest RR. In 2022, the Bayesian spatial CAR Leroux Model with Inverse Gamma prior (1;0.01) is the best model, with DKI Jakarta Province still having the highest RR, while Bali still has the lowest RR.